Anwar Ibrahim penghulu Melayu baru? - Taza Tahir (Kota Kinabalu, Sabah : Camford Cooperation Sdn. Bhd., 1998)
On Anwar Ibrahim's political downfall.
Koleksi sumbangan Tun Ahmad Sarji Abdul Hamid
Keywords: Anwar Ibrahim, -- Dato' Seri, -- 1947-; Malaysia -- Politics and government